Leg Symptoms, the Ankle-Brachial Index, and Walking Ability in Patients With Peripheral Arterial Disease - McDermott, Mary McGrae (Blackwell Science Inc, 1999)
OBJECTIVE: To determine how functional status and walking ability are related to both severity of lower extremity peripheral arterial disease (PAD) and PAD-related leg symptoms. DESIGN: Cross-sectional study. SETTING: Academic medical center. PARTICIPANTS: Patients aged 55 years and older diagnosed with PAD in a blood flow laboratory or general medicine practice (n=147). Randomly selected control patients without PAD were identified in a general medicine practice (n=67). MEASUREMENTS: Severity of PAD was measured with the ankle-brachial index (ABI). All patients were categorized according to whether they had (1) no exertional leg symptoms; (2) classic intermittent claudication; (3) exertional leg symptoms that also begin at rest (pain at rest), or (4) exertional leg symptoms other than intermittent claudication or pain at rest (atypical exertional leg symptoms). Participants completed the 36-Item Short-Form Health Survey (SF-36) and the Walking Impairment Questionnaire (WIQ). The WIQ quantifies patient-reported walking speed, walking distance, and stair-climbing ability, respectively, on a scale of 0 to 100 (100 = best). MAIN RESULTS: In multivariate analyses patients with atypical exertional leg symptoms, intermittent claudication, and pain at rest, respectively, had progressively poorer scores for walking distance, walking speed, and stair climbing. The ABI was measurably and independently associated with walking distance (regression coefficient = 2.87/0.1 ABI unit, p = .002) and walking speed (regression coefficient = 2.09/0.1 ABI unit, p = .015) scores. Among PAD patients only, pain at rest was associated independently with all WIQ scores and six SF-36 domains, while ABI was an independent predictor of WIQ distance score. CONCLUSIONS: Both PAD-related leg symptoms and ABI predict patient-perceived walking ability in PAD.